Neural Correlates of Decisions in Quasi-Realistic, Affective Social Interactions in Individuals With Violence-Related Socialization - Wiechert, Juliana; Janzen, Axel; Achtziger, Anja; Fehr, Thorsten (Frontiers in Behavioral Neuroscience, 2021)
Appropriate social behavior in aggressive-provocative interactions is a prerequisite for a peaceful life together. In previous research, dysfunctions of the control of aggression was suggested to be modulated by enhanced bottom-up (sub-cortically driven) and reduced top-down (iso-cortical frontal) processing capability. In the present study, two groups of individuals with enhanced (EG) and normal (NG) experiences of violent action during their socialization made binary behavioral decisions in quasi-realistic social interactions. These interactions were presented in short video-clips taken from a first-person perspective. The video-clips showed social interaction scenarios oriented on realistic everyday life situations. Behavioral data supported the distinct affective qualities of three categories of the social interactions. These categories were labelled as aggressive provocative, social positive, and neutral social interactions. Functional neuroimaging data showed extended activation patterns and higher signal intensity for the NG compared to the EG in lateral inferior frontal brain regions for aggressive provocative interactions. Furthermore, the peri-aqueductal gray produced enhanced activations for affective interaction scenarios (i.e., aggressive provocative and social positive) in both groups and as a trend with medium effect size for neutral interactions in the EG. As individuals in the EG did not show open aggression during the fMRI investigation, we concluded that they applied individual self-control strategies to regulate their aggressive impulses immediately. These strategies appeared to be rather top-down regulated through dorsal frontal brain areas. The predominant recruitment of hetero-modal cortices during the neural processing of complex social interactions pointed to an important role of individual learning history and socialization with differing levels of violent experiences as crucial modulators in convicts. Our data suggest that building or strengthening an association between prototypical social contexts (e.g., aggressive provocative interactions) and appropriate behavior as a response to it provides a promising approachto re-socialize successfully people with a delinquent history.